Comparison of Stock Performance Based on Ethical Investment: Evidance on JII and SRI-KEHATI Indices - Jeihan Ali Azhar; Resti Wulandari (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to analyze and compare the performance of the Islamic stock portfolio represented by the JII index and ethical investment represented by the SRI-KE-HATI index by measuring the Risk Adjustment Return Index through the Sharpe index, Treynor index, and Jensen Index differential return and appraisal ratio. The data analysis of this research consists of five parts, namely descriptive analysis, analysis of stock performance, with three methods, namely Sharpe, Treynor, and Jensen.differential return and appraisal ratio and Multiple Comparison Test. Based on the comparison of the performance of JII and SRI-KEHATI stocks in 2014-2019, it can be concluded that the overall method of Sharpe, Treynor and differential return shows a negative performance value, which means that the performance is not good, whereas when measured using the Jensen method and Appraisal Return shows positive performance value, which means good performance. When compared between the performance of JII and SRI-KEHATI shares, there is a difference between the performance of the JII and SRI-KEHATI Indices during the study period